2019
DOI: 10.3390/ma12203445
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Strength and Ductility in Magnesium Matrix Composites Reinforced by a High Volume Fraction of Nano- and Submicron-Sized SiC Particles Produced by Mechanical Milling and Hot Extrusion

Abstract: In the present study, Mg nanocomposites with a high volume fraction (10 vol %) of SiC particles were fabricated by two approaches: mechanical milling and mixing, followed by the powder consolidation steps, including isostatic cold pressing, sintering, and extrusion. A uniform distribution of the high content SiC particles in a fully dense Mg matrix with ultrafine microstructure was successfully achieved in the mechanically milled composites. The effect of nano- and submicron-sized SiC particles on the microstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…According to the EDS results in Figure 4 and Figure 5 , it can be known that SiC was found, which agreed well with the OM observations and XRD results in Figure 2 and Figure 3 . There was no reaction between the iron matrix and SiC, and similar results were also found in other kinds of metal-based materials reinforced by SiC [ 12 , 13 , 14 , 15 , 16 ], which means SiC is a stable reinforcer. As to Figure 5 b,d, it shows that Ti was detected in the reinforcing particle area; however, Al was found in the whole observation area.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…According to the EDS results in Figure 4 and Figure 5 , it can be known that SiC was found, which agreed well with the OM observations and XRD results in Figure 2 and Figure 3 . There was no reaction between the iron matrix and SiC, and similar results were also found in other kinds of metal-based materials reinforced by SiC [ 12 , 13 , 14 , 15 , 16 ], which means SiC is a stable reinforcer. As to Figure 5 b,d, it shows that Ti was detected in the reinforcing particle area; however, Al was found in the whole observation area.…”
Section: Resultssupporting
confidence: 80%
“…This sintering process, which is normally done in a few minutes, makes manufacturing feasible with low costs and produces excellent material properties due to the short processing time [ 5 , 8 ]. With a good load-bearing effect in composites, SiC is a very common reinforcing agent in many metal base materials, such as iron [ 5 , 9 ], aluminum [ 10 , 11 , 12 , 13 ], magnesium [ 14 , 15 ], nickel [ 16 , 17 ], and zinc [ 18 ]. Our previous research results showed that SiC has the best enhancement effect compared with the common candidate reinforcements, such as TiC, TiN, and Cr 3 C 2 in IMCs [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kamrani et al. 29 reported that uniformly distributed nanoparticles enhance the elastic modulus of the composite by behaving like a homogenous structure and resisting the plastic deformation at lower stress. Also, Slipenyuk et al.…”
Section: Resultsmentioning
confidence: 99%
“…The advantageous properties could be attained only if the reinforcements are distributed homogeneously and not clustered in the matrix. According to the literature available [ 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 ], limited research has been performed on CNT-reinforced MMCs due to difficulties in fabricating and dispersion of CNTs in the matrix. Most studies investigated the fabrication methods such as the casting process and powder metallurgy for developing Mg-based alloy [ 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 ,…”
Section: Summary and Future Road Mapsmentioning
confidence: 99%